A pediatric phase 1 trial of vorinostat and temozolomide in relapsed or refractory primary brain or spinal cord tumors: A children's oncology group phase 1 consortium study. Issue 9 (28th March 2013) - Hummel, Trent R.; Wagner, Lars; Ahern, Charlotte; Fouladi, Maryam; Reid, Joel M.; McGovern, Renee M.; Ames, Matthew M.; Gilbertson, Richard J.; Horton, Terzah; Ingle, Ashish M.; Weigel, Brenda; Blaney, Susan M.
Abstract Purpose We conducted a pediatric phase I study to estimate the maximum tolerated dose (MTD), dose‐limiting toxicities (DLT), and pharmacokinetic properties of vorinostat, a histone deacetylase (HDAC) inhibitor, when given in combination with temozolomide in children with refractory or recurrent CNS malignancies. Patients and Methods Vorinostat, followed by temozolomide approximately 1 hour later, was orally administered, once daily, for 5 consecutive days every 28 days at three dose levels using the rolling six design. Studies of histone accumulation in peripheral blood mononuclear cells were performed on Day 1 at 0, 6, and 24 hours after vorinostat dosing. Vorinostat pharmacokinetics (PK) and serum MGMT promoter status were also assessed. Results Nineteen eligible patients were enrolled and 18 patients were evaluable for toxicity. There were no DLTs observed at dose level 1 or 2. DLTs occurred in four patients at dose level 3: thrombocytopenia (4), neutropenia (3), and leucopenia (1). Non‐dose limiting grade 3 or 4 toxicities related to protocol therapy were also hematologic and included neutropenia, lymphopenia, thrombocytopenia, anemia, and leucopenia. Three patients exhibited stable disease and one patient had a partial response. There was no clear relationship between vorinostat dosage and drug exposure over the dose range studied. Accumulation of acetylated H3 histone in PBMC was observed after administration of vorinostat. Conclusion Five‐day cycles of vorinostat in combination with temozolomide are well tolerated in children with recurrent CNS malignancies with myelosuppression as the DLT. The recommended phase II combination doses are vorinostat, 300 mg/m2/day and temozolomide, 150 mg/m2/day. Pediatr Blood Cancer 2013;160:1452–1457. © 2013 Wiley Periodicals, Inc.